2011
DOI: 10.1523/jneurosci.0492-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Optimal and Suboptimal Use of Postsaccadic Vision in Sequences of Saccades

Abstract: Saccades are imprecise, due to sensory and motor noise. To avoid an accumulation of errors during sequences of saccades, a prediction derived from the efference copy can be combined with the reafferent visual feedback to adjust the following eye movement. By varying the information quantity of the visual feedback, we investigated how the reliability of the visual information affects the postsaccadic update in humans. Two elements of the visual scene were manipulated, the saccade target or the background, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A similar finding has been reported by Munuera et al (2009); they found that the corrective saccade with visual feedback only compensate for 70% of intrasaccadic target jump (20% of 18° target eccentricity) in a modified double-step paradigm. Their following experiment (Morel, Deneve & Baraduc, 2011) also showed incomplete corrections (with gain lower than the main saccade gain). The reason for this incomplete correction is still unknown, though it may again be a time optimal strategy to avoid overshooting because of inherent noise.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A similar finding has been reported by Munuera et al (2009); they found that the corrective saccade with visual feedback only compensate for 70% of intrasaccadic target jump (20% of 18° target eccentricity) in a modified double-step paradigm. Their following experiment (Morel, Deneve & Baraduc, 2011) also showed incomplete corrections (with gain lower than the main saccade gain). The reason for this incomplete correction is still unknown, though it may again be a time optimal strategy to avoid overshooting because of inherent noise.…”
Section: Discussionmentioning
confidence: 91%
“…The reason for this incomplete correction is still unknown, though it may again be a time optimal strategy to avoid overshooting because of inherent noise. On the other hand the calculation might also be based not only on the perceived visual error, but also on the predicted visual error (Morel et al, 2011, Vaziri, Diedrichsen & Shadmehr, 2006, Wong & Shelhamer, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it remains an open question how our findings might translate to more cluttered visual scenes typically encountered in everyday life. Previous studies indicate that the structural gist of background information is indeed taken into account for matching of visual space across saccades [ 44 , 45 ]. Reliability of such information will be more difficult to parameterize and the visuomotor system may additionally incorporate a non-flat prior on (the implausibility of) visual background jumps during eye movements [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in human subjects, up to 20% of secondary saccades were not directed to the saccade target. These secondary saccades were also considered as secondary saccades ( Morel et al, 2011 ). Therefore, we included all secondary saccades for further analysis.…”
Section: Methodsmentioning
confidence: 99%